Comparative analysis of changes in retinal layer thickness following femtosecond laser-assisted cataract surgery and conventional cataract surgery - Dongheon Surl; Seungmin Kim; Sangyeop Kim; Tae-Im Kim; Kyoung Yul Seo; Ikhyun Jun (BMC Ophthalmology, 2024)
Abstract Background To investigate the influence of femtosecond laser-assisted cataract surgery (FLACS) on macula by examining changes in retinal layers after FLACS and to compare these changes with those after conventional cataract surgery (CCS). Methods This study included 113 unrelated Korean patients with age-related cataract who underwent CCS or FLACS in Severance Hospital between September 2019 and July 2021. Optical coherence tomography was performed before and 1 month after surgery. The total retinal layer (TRL) was separated into the inner retinal layer (IRL) and outer retinal layer (ORL); moreover, the IRL was subdivided into the retinal nerve fiber layer, ganglion cell layer, inner plexiform layer, inner nuclear layer (INL), outer plexiform layer, and outer nuclear layer. We performed between-group comparisons of the postoperative thickness in each retinal layer and the postoperative differences in retinal thickness. The average retinal thickness of the four inner macular ring quadrants was used for comparative analysis. Results Compared with the CCS group, the FLACS group exhibited a thicker ORL (P = 0.004) and a thinner INL (P = 0.007) after surgery. All retinal layer thickness values showed significant postoperative changes regardless of the type of surgery (P < 0.05). The postoperative increase in TRL and IRL thickness was significantly smaller in the FLACS group than in the CCS group (P = 0.027, P = 0.012). Conclusions The 1-month postoperative retinal changes were less pronounced in the FLACS group than in the CCS group.